An ethnography of crime in Belfast - Brewer, John; Lockhart, William H.; Rodgers, Paula (Statistical and Social Inquiry Society of Ireland, 1996)
In an earlier paper to the Statistical and Social Inquiry Society of Ireland in Dublin, we provided a statistical comparison of trends in indictable crime in both parts of Ireland between 1945 and 1993 set against other survey data on crime, trends in specific offences and geographical variations in crime trends. This drew on data from our larger research project on crime in Ireland since the Second World War. In this paper we intend to report on the ethnographic research conducted as part of the same project. The rationale behind the ethnographic study of crime in two police sub-divisions of Belfast was to use the benefits of the ethnographic method to supplement the quantitative approach to crime trends. The data are drawn from two closely matched police sub-divisions in Belfast, Castlereagh in East Belfast and Woodburn in the West of the city, the former largely Protestant and the latter largely Catholic, reproducing the city?s communal spatial divide. Each sub-division also comprises a mix of inner city deprivation and suburban splendour. Fieldwork was conducted over a twelve-month period between 1994 and 1995. The paramilitary ceasefire was called four months into fieldwork.
Read before the Society, 14 March 1996
Keywords: Ethnography; Belfast communities; 314.15